2016
DOI: 10.1177/0093854815628026
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Discrimination and Prosecution

Abstract: Unwarranted disparity taking place at the stage of prosecution has long been an interest for sentencing researchers. Research exploring the effect of offender race on prosecutorial decisions, however, has produced conflicting and inconclusive results. Some studies concluded that minority offenders faced more unfavorable outcomes than White offenders, whereas others found no significant impact of race/ethnicity in the prosecution process. Still others found a minority advantage. Given these inconsistencies, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 71 publications
1
49
0
Order By: Relevance
“…31 A 2016 meta-analysis assessed empirical findings from 26 studies involving a total of 86,877 criminal cases. 32 Minority offenders were 9% more likely to be charged or fully prosecuted than white offenders. 33 To the contrary, a few studies have found null results or even a racial disparity in favor of minorities.…”
Section: A Effects Of Racementioning
confidence: 97%
“…31 A 2016 meta-analysis assessed empirical findings from 26 studies involving a total of 86,877 criminal cases. 32 Minority offenders were 9% more likely to be charged or fully prosecuted than white offenders. 33 To the contrary, a few studies have found null results or even a racial disparity in favor of minorities.…”
Section: A Effects Of Racementioning
confidence: 97%
“…For example, studies have indicated that young African American boys are viewed by others as older and less innocent compared to non-Hispanic white peers of the same age [40]. Findings such as these indicate how bias and racism can be implicated in police arrest decisions, prosecutorial charges, and judicial sentencing [40][41][42]. These systemic injustices and hostilities toward minority youth may instigate behaviors which commonly lead to labels of ODD and CD, perpetuating a cycle of structural racism: If minority youth perceive others viewing them as older, more dangerous, more aggressive, and less innocent than they really are, they may respond with aggressive and defiant behaviors based on these perceptions [40].…”
Section: Systemic Biases and Structural Racismmentioning
confidence: 99%
“…Whites have reported more positive perceptions of their personal treatment by legal authorities than Latino and Black youth (Buckler, Wilson, Hartley, & Davila, 2011; Gau & Brunson, 2010; Tartar et al, 2012). These perceptions are likely due to real disparities in treatment and outcomes among minority groups in the justice system, with research indicating that minority offenders are more likely to be arrested, face greater odds of being charged and prosecuted, and are sentenced more harshly than their white counterparts (Bonnie, Johnson, Chemers, & Schuck, 2013; Gau & Brunson, 2010; Lytle, 2014; Mitchell, 2005; Wu, 2016). Although prior experience with the justice system has been less well studied, there is some evidence that individuals with more convictions perceive personal contacts as less just (Otto & Dalbert, 2005).…”
Section: Implications For Procedural Justicementioning
confidence: 99%